INTERNSHIP IN ACCOUNTING–ITS VALUE AS A TRAINING FOR ADMINISTRATIVE POSITIONS. - Frederick, M. L. (The Accounting Review, 1927)
Abstract It is generally recognized that one of the leading factors contributing to the present high level of prosperity is the economy from large-scale production. The reduction of overhead and the lowering of unit costs due to the manufacture of commodities in large quantities has brought within reach of the average workman comfort. which were sheer luxuries a generation ago. This would scarcely have been possible under the sole-proprietorship and partnership forms of organization, as no small group of investors would have been able to furnish sufficient capital to finance the requisite volume of business. It has been the corporation, under the guidance of farsighted executives, which has contributed so largely to this progress. This change in the general aspect of business (with the scientific approach to problems of finance, production, and marketing which is now required) has placed business on the plane of a profession; and colleges and universities have recognized this by establishing departments of business administration with curricula designed to train men as leaders in this profession.